2017
DOI: 10.1111/ecc.12641
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors’ attitudes towards and knowledge of physical activity, sources of information, and barriers and facilitators of engagement: A qualitative study

Abstract: Limited literature exists on attitudes towards, knowledge of and where cancer survivors seek information on physical activity. This study aimed to address these gaps in the literature. Interviews were conducted with 19 UK‐based adult cancer survivors. Interviews covered participants’ knowledge of the relationship between physical activity and cancer, sources of information and attitudes towards physical activity following their cancer treatment. Data were analysed using Thematic Analysis. Key themes included “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 32 publications
7
80
0
Order By: Relevance
“…Motivating factors included their experience of benefits from physical activity, the ability to use physical activity as a mental distraction and the desire to use physical activity as a means to maintain “normality” in life. These findings are generally consistent with prior work in lung cancer and palliative care populations reporting the majority of patients are interested in and feel able to participate in exercise programmes (Lowe, Watanabe, Baracos, & Courneya, ) and a desire for more support (Smith et al, ). One important, relatively novel, finding in our study was the identification that patients desire assistance with behavioural change.…”
Section: Discussionsupporting
confidence: 87%
“…Motivating factors included their experience of benefits from physical activity, the ability to use physical activity as a mental distraction and the desire to use physical activity as a means to maintain “normality” in life. These findings are generally consistent with prior work in lung cancer and palliative care populations reporting the majority of patients are interested in and feel able to participate in exercise programmes (Lowe, Watanabe, Baracos, & Courneya, ) and a desire for more support (Smith et al, ). One important, relatively novel, finding in our study was the identification that patients desire assistance with behavioural change.…”
Section: Discussionsupporting
confidence: 87%
“…Behaviour change also appeared impeded by cancer‐related side effects and the influence of the cancer experience on the management of pre‐existing comorbidities. Similar findings have been reported elsewhere . Cancer survivors with comorbid diseases often prioritise one chronic condition or symptom over another, and many struggle to integrate various self‐care strategies into their routine .…”
Section: Discussionsupporting
confidence: 84%
“…Participants also reported uncertainty about whether any changes they had made were appropriate or sufficient for cancer survivors and did not want to make changes without explicit guidance from their HCP. Previous studies have also reported that participants received little information from health professionals relating to engaging in PA, with participants searching for information via media and websites . Confusion about how to implement changes is likely to reduce motivation to make lifestyle changes .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given the methodological quality and risk of bias with regard to Chou et al, it is perhaps unwise to put substantial weight behind this finding. With several qualitative evidences reporting that a barrier to PA is fatigue and Cramp and Byron‐Daniel arguing that aerobic exercise is beneficial in managing fatigue, it is clear that fatigue plays a role in cancer and adherence to PA. Engaging in PA is a huge barrier with evidence suggesting that being able to live well and engaging or reengaging in activities such as PA is a complex and challenging issue …”
Section: Discussionmentioning
confidence: 99%